Applications of the 'fair hearing' norm in ECHR article 6(1) to civil proceedings : with special emphasis on the balance between procedural safeguards and efficiency /: with special emphasis on the balance between procedural safeguards and efficiency. ([2016]) - Settem, Ola Johan
No abstract available